Correlation between Surface Engineering and Deformation Response of Some Natural Polymer Fibrous Systems. Issue 2 (June 2018) - Vrinceanu, Narcisa; Guignard, Mirela Iorgoaiea; Campagne, Christine; Giraud, Stephane; Prepelita, Raluca Ioana; Coman, Diana; Dan Petrescu, Valentin; Dumitrascu, Dan Dumitru; Ouerfelli, Noureddine; Suchea, Mirela Petruta
Surfaces of bamboo derived cellulosic fibrous systems have been modified by air-plasma treatment. Their deformational response was studied to establish the relationship between their three-dimensional profile and permanent deformation as a measure of their comfort properties since the fibrous system made of natural polymer comes into contact with the skin. The composite should have a permanent deformation close to zero, in order to be, in terms of dimensions, as stable as possible. By analyzing the area of 1 cm 2 using a Universal Surface Tester (UST), different 3D surface diagrams and surface roughness values were obtained. This type of surface investigation provides relevant information about the permanent deformation response of the studied surface, for comfort purposes. The deformation responses and roughness levels were studied (the roughness being the parameter quantifying the 3D geometry of the systems surface). The effect of air-plasma surface modification on the deformation response of bamboo derived cellulosic fibrous systems and optimization of their 3D surface structure to enhance comfort-related properties proved to be substantial. The surface modifications induced by air-plasma treatment are in a good correlation with the mechanical behavior. As expected, the roughness levels of samples studied using ball sensors are higher than those of specimens scanned using a papillary sensor. Knitted polymer fibrous matrix T1 shows a roughness level of 773 μm resulting from analyses using the ball sensor, while using the papillary sensor it was 102 μm, 86.8% less than before. The analysis of the dimensional stability of knitted polymer fibrous systems was performed by scanning with the papillary sensor, since it provides information comparable with human perception concerning the architecture of the sample surfaces.